Exploring Of Rural And Urban Attitudes In The New Normal Era Of COVID 19: A Study In Acehnese Community - Safuwan Amin; Rahmia Dewi (International Journal of Educational Research & Social Sciences, 2021)
This article descript reports on attitudes of communities those who live in rural and urban citizens in the new normal Covid-19 era by a sample of Aceh Utara district and the city of Lhokseumawe, Aceh province, Indonesia. Attitudes are generally understood by people as individual evaluations in a positive or negative sense for objects, events, situations, or other aspects, and allow individuals to predict and change their behavior in life. The data collection was done through direct observation, in-depth interviews, and FGD. The findings of the study show that the attitudes of rural and urban residents are no significant differences in the aspects of knowledge/experience and understanding of the developing reality. However, from the spotlight, the tendency of citizens' behavior looks different between what is known and understood with the appearance of behavior, where the behavior of rural residents ignores the adaptation of the new normal rules, and urban residents generally follow the new normal rules for the Covid-19.